Implementation of the Synergetic Potential of Artistic Communication as an Innovative Strategy of Art Education - Bilova, Nataliia; Novska, Olena; Volkova, Yuliia (Journal of History Culture and Art Research, 2020)
The research is devoted to substantiation of the synergetic paradigm of art education. The aim of the article is to study the nature and manifestation of the synergetic potential of artistic communication in music and choreographic education in the context of creating artistic and pedagogical influence aimed at personal-spiritual and professional development of the individual. The article uses the theoretical research methods: analysis, synthesis, systematization, generalization, abstraction and extrapolation. The essence of communication as the main category of art universe, in particular, art education, is defined. The notion of artistic communication as a mutually transforming process of interaction with an artistic image on the basis of this image is actualized. It is indicated that synergetics is the methodological basis of the new scientific and pedagogical paradigm. It is established that the synergetic effect of artistic communication in the educational space is manifested through the multiplicity, ambiguity and inexhaustibility of the process of comprehension, interpretation and creation of artistic image. The essence of the synergetic potential is substantiated as a set of resources and factors of improved additional new result of creative cooperation, which is realized through a combination of rational and irrational, artistic and technical, subjective and objective processes. The ways of implementation of the synergetic potential of artistic communication in the pedagogical process of higher education institutions are reflected. Sign-communicative systems of musical and choreographic language are considered. The use in the process of art education of creative synthetic methods based on a combination of musical and choreographic art (the method of creating art projects, the method of eurythmy, the method of sensory-resonance improvisation) is suggested. The effect of their application in realization of the synergetic potential of artistic communication in the process of art education is determined.